Honeybees (Apis mellifera) collect latex of Azores bellflowers (Azorina vidalii, Campanulaceae) - Weissmann, Julie A. (2016)
Submitted by RUA REPOSITORIO (repositorio@uac.pt) on 2016-11-15T14:11:45Z No. of bitstreams: 1 LMS_Weissman_Schaefer_ARQ2015_N32_ShortCom.pdf: 678176 bytes, checksum: 460ae604a69f2670a5ea339cdf2bbcbb (MD5)